Non-contact evaluation of pigs’ body temperature under various infrared sources - Hoc Thai Nguyen; Tien Xuan Dao; Duong Tri Ngo (Institute of Advanced Engineering and Science, 2023)
The purpose of this study is to verify the feasibility of using an infrared camera to measure the surface temperature and then estimate the core body temperature of pigs under various infrared sources. We first conducted experiments with pig-body temperature measurement by an infrared camera. Then we have tried to increase the accuracy rate in estimating the core body temperature of pigs by measuring the temperature of moving pixels. We concluded that the relation between the core body temperature and the estimated pig-body temperature was y = 1.0392x−0.6621 with no static infrared source in the field view of infrared camera. With the existence of heat lamps in the field of view of the infrared camera, the relation was y = 1.0248x − 0.0921. With both the root mean square error and the mean absolute error lower than 1.12 ◦C, the experimental simulation results show that the proposed method is feasible and effective in fast and non-contact evaluation of pigbody temperature under various infrared sources.